A comparison of two methods for moving through a virtual environment: walking in place and interactive redirected walking - Banakou, Domna; Slater, Mel (Frontiers in Virtual Reality, 2023)
Moving through a virtual environment that is larger than the physical space in which the participant operates has been a challenge since the early days of virtual reality (VR). Many different methods have been proposed such as joystick based navigation, walking in place where the participant makes walking movements but is stationary in physical space, and redirected walking where the environment is surreptitiously changed giving the illusion of walking in a long straight line in virtual space but maybe a circle in physical space. Each type of method has its problems, ranging from simulator sickness through to still requiring more physical space than is available. Stimulated by the COVID-19 lockdown we developed a new method of locomotion that we refer to as interactive redirected walking. Here the participant really walks, but when reaching a boundary rotates the virtual world so that continuation of walking is always within the physical boundary. We carried out an exploratory study to compare this method with walking in place with respect to presence using questionnaires and also with qualitative responses based on comments written by the participants that were subject to sentiment analysis. We found, surprisingly, that smaller physical boundaries favor interactive redirected walking, but for boundary lengths more than about 7 adult paces the walking in place method was preferred.